Simuliranje preizkusa težke nesreče Phebus FPT1 s programom MELCOR - Leskovar, Matjaž (Strojniški vestnik, 2006)
As part of the OECD International Standard Problem No. 46, the thermal-hydraulic, fuel-degradation and aerosol phenomena, which occurred in the bundle and circuit of the Phebus facility during the degradation phase of the Phebus FPT1 experiment, were simulated with two versions of MELCOR 1.8.5 (QZ and RE). The input model was developed by strictly following the recommendations on noding and the use of the default parameters provided in the ISP-46 Specification Report. Special attention was given to the modelling of the specifics of the Phebus facility. A comparison of the simulation results and the experimental measurements showed good agreement for the thermal-hydraulic variables and satisfactory agreement for the total releases for most radio-nuclides, whereas the radio-nuclide depositions in the steam generator were overestimated. The timing of the key events was relatively wellpredicted. The differences between the simulation results of both MELCOR versions were negligible for the thermal-hydraulic variables, small for the radio-nuclide releases and the timing of the key events, but significant for the radio-nuclide depositions and the bundle degradation. In general, the results of the newer MELCOR 1.8.5 version RE show better agreement with the experimental measurements.
Keywords: jedrska varnost; reaktorji; modeliranje; simuliranje; nezgode; računalniški program Melcor